Implementasi Value Creation pada Klinik Kecantikan dan Skincare di Klinik Pratama Shaletta - Icha Pramitha Hamzah; Muhammad Basir; Asnany Asnany (Publikasi Indonesia, 2025)
This study investigates the implementation of value creation in Klinik Pratama Shaletta, aiming to identify its specific forms, explore its strategic importance in sustaining competitiveness, and analyse the processes through which it is applied. A qualitative descriptive design was employed, utilizing in-depth interviews, direct observations, and document analysis. Data were examined using Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing. Findings reveal that value creation in the clinic is manifested through four interrelated dimensions: functional value, emotional value, social/symbolic value, and economic value. These are shaped by internal factors such as service quality, staff competence, brand image and external factors, including market trends and evolving customer needs. The study concludes that a consistent and adaptive approach to value creation fosters stronger customer loyalty and enhances the clinic’s market position. Strategic recommendations include diversifying services tailored to individual needs, integrating advanced technologies, and reinforcing customer communities to build long-term engagement.